Modulação da via das MAPKs pelo Vaccinia virus: envolvimento da proteína viral B14 e papel das proteínas celulares JNK e Spir-1 - Alice Abreu Torres (2016)
A successful viral replication relies both on cell signaling pathways subversion and evasion from host antiviral responses. Therefore, in favor of its replication and spread, Vaccinia virus (VACV) is well known for its ability to activate MAPK/AP-1 pathway, as well as to encode several immunomodulatory proteins including many NF-kB inhibitors. Unlike NF-kB, little is known about the MAPK/AP-1 modulation during VACV infection. Knowing that both transcriptional factors share upstream activators, we have decided to investigate whether six known VACV inhibitors of NF-κB (A46, A49, A52, B14, K7 and N1) also have a role on MAPK/AP-1 modulation. Our results showed that A52, B14 and K7 proteins were able to activate the AP-1, both during cell transfection and infection with VACV knockout for A52R, B14R (VACV-delB14) and K7R genes, respectively. We focused our study on the viral protein B14 once it had the major ability of AP-1 stimulation. B14 is able to activate the MAPK during VACV infection, specifically JNK and its substrates c-Jun and ATF-2, since the phosphorylation of these three proteins is reduced during infection with VACV-delB14 when compared to wild-type VACV. It is known that JNK is not important for VACV replication, however, it does participate in cytoskeletal reorganization, viral spread and actin tail formation. In order to elucidate how JNK regulates actin tail formation, we have decided to investigate the role of the actin nucleator Spir-1, a known substrate of JNK. By coimmunoprecipitation, we revealed that both proteins associate during VACV infection. Furthermore, as observed with JNK, viral spread, but not to viral replication, was affected in murine embryonic fibroblasts (MEFs) deficient in Spir-1 or HeLa cells transfected with Spir-1 siRNA when compared to wild-type MEFs and cells transfected with control siRNA, respectively. Also, our results suggested that deficiency of JNK or Spir-1 leads to a reduction in VACV-induced actin tails size. Taken together, these data have added new viral players that participate in the modulation of MAPKs during VACV infection, as well as have contributed to clarify additional mechanisms by which JNK can contribute to the viral spread.